Sintering Kinetics and Interfacial Heat Transfer Process of Binary Alloy Nanoparticles Catalysts: Molecular Dynamics Simulation - Deng, Shengwei; Shi, Feng; Huang, Yudi; Qiu, Chenglong; Wang, Jian-guo (Industrial & engineering chemistry research, 2024)
The thermal stability of supported alloy nanocatalysts is a crucial factor limiting the lifespan of catalysts. In this study, molecular dynamics (MD) simulations were employed to investigate the interface heat transfer and sintering kinetics of binary alloy nanoparticles composed of Pt, Ni, and Fe supported on graphene substrates. Analysis of the crystalline distribution, radial distribution function (RDF), and potential energy variations of the supported particles revealed that significant differences in the atomic radii and interaction energies (potentials) of the metals could lead to the formation of core–shell structures in alloy nanoparticles, whereas the reverse scenario might result in disordered alloy structures, with the particle structure closely tied to its thermal stability. Simulation results of the heat transfer process indicated that core–shell structures could enhance the cooling rate of the particles. Additionally, metal with superior thermal conductivity could increase the contact area between the particles and the substrate, thereby enhancing the interfacial thermal conductivity. Further analysis of the shrinkage of each alloy revealed that when a more stable (judged by the maximum shrinkage of the particles within the same time) metal comprised a higher proportion of the alloy, the particles exhibited greater stability and were less prone to sintering.